2016
DOI: 10.1001/jamapsychiatry.2016.0076
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mindfulness-Based Cognitive Therapy in Prevention of Depressive Relapse

Abstract: Importance Relapse prevention in recurrent depression is a significant public health problem, and antidepressants are the current first-line treatment approach. Identifying an equally efficacious nonpharmacological intervention would be an important development. Objective To conduct a meta-analysis on individual patient data to examine the efficacy of mindfulness-based cognitive therapy (MBCT) compared with usual care and other active treatments, including antidepressants, in treating those with recurrent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
442
5
31

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 642 publications
(505 citation statements)
references
References 41 publications
27
442
5
31
Order By: Relevance
“…Furthermore, comparisons with active treatments suggest a reduced risk of depressive relapse within a 60-week follow-up period (hazard ratio 0.79, 95% confidence interval 0.64 to 0.97). 18 Usual care in these studies refers to normal health service provision in the nations in which the studies were conducted; the active comparisons were typically maintenance antidepressants.…”
Section: Mindfulness-based Cognitive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comparisons with active treatments suggest a reduced risk of depressive relapse within a 60-week follow-up period (hazard ratio 0.79, 95% confidence interval 0.64 to 0.97). 18 Usual care in these studies refers to normal health service provision in the nations in which the studies were conducted; the active comparisons were typically maintenance antidepressants.…”
Section: Mindfulness-based Cognitive Therapymentioning
confidence: 99%
“…1,10 Moreover, such services would provide patients with access to a therapy that supports the development of skills that can support recovery in the long term, 18 reduce suffering for patients and their families and reduce the costs for the NHS. 10 MBCT is fully aligned with an approach to integrated physical and mental health care, and emerging narratives that chronic physical health problems and mental health require preventative, well-being-oriented approaches whereby people are supported in taking responsibility for their long-term self-management and care with input from health-care services when and if required.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…MBCT teaches participants to recognize and disengage from maladaptive automatic cognitive patterns, and to develop a nonjudgmental and compassionate attitude toward their own cognitions and feelings. MBCT has been demonstrated to be effective in reducing relapse (Kuyken et al., 2016). In addition, it has been shown that MBCT reduces depressive symptoms in currently depressed patients (Strauss, Cavanagh, Oliver, & Pettman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The second lowest level of depressive symptoms was observed from the Roman Catholic respondents, a religion that has monastic retreat programs. The differences in depression levels could be due to differences in treatment programs: meditation and mindfulness-based cognitive therapy (MBCT) versus clinical psychology Helmes and Ward 2017;Maxwell and Duff 2016;Davidson 2016;Kuyken et al 2016).…”
Section: Religious Variations In Depressive Symptomsmentioning
confidence: 99%